Vitamin D-deficiency states in the genesis of woman reproductive health disorders - Т. Ф Татарчук; К. Д. Дейнюк; О. В. Занько; Т. І. Юско; В. О. Тарнопольська (Publishing House TRILIST, 2018)
Thanks to the continuous scientific and creative search for researchers over the past almost hundred years, vitamin D preparations are finding increasing uses, from classical prevention of rickets and osteomalacia to the prevention of malignant neoplasms and mental illnesses. The article discusses the use of vitamin D in the genesis of women reproductive health disorders, as well as its impact on the condition of women in different periods - childhood, the age of menarche and adolescence, the reproductive age and the menopause. The influence of vitamin D deficiency on a number of diseases, in particular, inflammatory diseases of the pelvic organs, breast pathology, hyperproliferative diseases is considered in detail. The results of authors' study, which confirms the normalization of vitamin D levels in patients who received the drug containing cholecalciferol, are indicative of its effectiveness in correcting vitamin D deficiency. As the authors of the article emphasize, encouraging patients to use preparations containing vitamin D and annual testing for D-status detection has the potential to become a modern method of preventing uterine fibroids, endometrial and breast cancer, obesity, and polycystic ovary syndrome (PCOS). Nutritional supplements and medicines containing cholecalciferol, which is the least toxic fat-soluble vitamin, with regular intake reduce the risk of progression of metabolic disorders in PCOS, promote the proper formation of pelvic bones in girls, prevent the development of postpartum depression and slow the aging and cognitive decline with age, quality of life in general. It is advisable to test for vitamin D (25(OH)D3) serum levels in a number of population categories, in particular, for women planning pregnancy, pregnant women and women with hyperproliferative diseases. When vitamin D deficiency is detected, it is necessary to use preparations containing cholecalciferol, with dosage depending on body weight and vitamin D content in the blood serum.